PEMANFAATAN METODE GAME BASED LEARNING SEBAGAI MEDIA EVALUASI PEMBELAJARAN MAHASISWA EKONOMI - Cut Risya Varlitya; Muhammad Riska (Majelis Pendidikan Aceh, 2023)
The study aims to analyze the utilization of learning activities with Game-Based Learning using the Quizizz Platform as a learning evaluation medium for students of the Development Economics Study Program, Faculty of Economics and Business, Syiah Kuala University. The method used is descriptive quantitative. Data was taken by observing the development of scores on the first quiz and changes that occurred in the scores on the second quiz from the results of the Quizizz evaluation. This method was applied to two courses, introductory macroeconomics, and the Indonesian Economy, totaling 58 students. The results of the study found that learning using Game-Based Learning through the Quizizz application was able to support improving student learning evaluation results, increasing achievement and activeness, and student involvement in the learning process.